Surface motif sensitivity of dual emissive gold nanoclusters for robust ratiometric intracellular imaging. Issue 52 (27th May 2020) - Lou, Xuefen; Yu, Fanfan; Cao, Zheng; Xu, Yue; Yang, Lina; Liu, Honglin
Abstract : Surface motif reconstruction-directed synthesis of novel dual-emissive gold nanoclusters showing a ratiometric fluorescence response toward valine and Cr 3+ . Abstract : Here, we report novel dual-emissive gold nanoclusters (d-Au NCs) that have two distinctive emissions (420 and 630 nm) under a single wavelength excitation. The two-stage formation mechanism evidences their sensitive response to valine and trivalent chromium ions (Cr 3+ ) in completely different spectral ratiometric modes in living cells with high contrast to successfully avoid signal fluctuations.